2004
DOI: 10.1179/030801804225012446
|View full text |Cite
|
Sign up to set email alerts
|

The researcher and the field assistant: a cross-disciplinary, cross-cultural viewing of positionality

Abstract: It is almost a given in the social sciences that the outcome of the research process is directly affected by the social makeup of both researcher and respondents. Researchers have been encouraged to engage in a reflective process so as to recognise the existence of multiple viewpoints, the partiality of their assessments and the situatedness of the knowledge they produce. As a natural scientist taking up social science research I accepted these ideas quite readily, and endeavoured to prepare myself by consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…In qualitative research (cf. Davies et al, 2004;Jootun, McGhee, & Marland, 2009) and disciplines such as ethnography (see e.g., Barz & Cooley, 2008;Pasquini & Olaniyan, 2004), researchers have argued that attempts to find 'objective' results are limited, especially if observations of other humans are involved and interpretative judgements need to be made. This has led to calls for more reflexivity in research, for critical discussions of the researcher's viewpoint and the acknowledgement of potential limitations related to it.…”
Section: Introductionmentioning
confidence: 99%
“…In qualitative research (cf. Davies et al, 2004;Jootun, McGhee, & Marland, 2009) and disciplines such as ethnography (see e.g., Barz & Cooley, 2008;Pasquini & Olaniyan, 2004), researchers have argued that attempts to find 'objective' results are limited, especially if observations of other humans are involved and interpretative judgements need to be made. This has led to calls for more reflexivity in research, for critical discussions of the researcher's viewpoint and the acknowledgement of potential limitations related to it.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, we confirmed the extent to which data collected by citizen social scientists might be (or not be) subject to those same problems documented for citizen biophysical science, including the problems of low reliability and of differences in observer capacities (Lukyanenko, Wiggins, and Rosser 2019;Kosmala et al 2016;Steger, Butt, and Hooten 2017;Brown and Williams 2019;Heiss and Matthes 2017;Janssens, Cecile, and Kraft 2012). We also consider here a concern that is central to contemporary social science discussions around data interpretation in community-based research: the effects of personal positionality on what is observed and how it is experienced and reported by researchers, research assistants, and other stakeholders in the research process (e.g., Muhammad et al 2014;Sultana 2007;Pasquini and Olaniyan 2004;Turner 2010;Mwambari 2019).…”
Section: Introductionmentioning
confidence: 99%
“…There has been considerable reflection given to the process of ethnographic fieldwork within the social sciences, particularly anthropology and geography: gaining access to informants (Lal 1996); self-positioning and reflexivity (Nast 1994;Pasquini and Olayinan 2004); recognizing power relations within and beyond the researcher (Hsiung 1996); and failed projects (England 1994). There has been considerably less research that concerns itself with what happens when researchers leave the field and later return for feedback and dissemination of results (Polzer 2007:4).…”
Section: Introductionmentioning
confidence: 99%